The Numerical Integration to Solutions for the Double-slip Model for the Deformation and Flow of Granular Materials - Nor Alisa, Mohd Damanhuri; Nor Aida Zuraimi, Md Noar (2016)
This poster presents a numerical integration to solutions for the plane-strain rigid-perfectly plastic deformation of a granular material in a container satisfying the stress-equilibrium conditions, the Coulomb yield criterion and the double-slip kinematic equations.